Computers and common sense - Hunt, Roger; Shelley, John (New York : Prentice-Hall International Ltd., 1988)
The text contains the essential material relevant to these three concepts. As the applications of the concepts increase in sophistication, it sometimes becomes necessary to stop and develop a particular topic so that its relationship to other, subsequent elements can be appreciated.
1. An introduction to computing -- 2. The basic anatomy of the computer -- 3. The microcomputer -- 4. The human-computer interface -- 5. Computer languages -- 6. Principles of programming -- 7. Introduction to computer and operating systems -- 8. Computer networks -- 9. Computer applications -- 10. Data processing -- 11. An introduction to systems analysis -- 12. The DP department and information centers -- 13. The social issues.
Includes bibliographical references and index.
Keywords: COMPUTERS